Gender Analysis of Students Motivation to Learn in Social Studies Classes in Elementary School - Nasha Indri Fazila; Nurdiansyah; Jennyta Caturiasari (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Students’ learning motivation based on gender and its correlation with gender representation in social studies instruction have not been extensively studied, particularly at the elementary school level in Indonesia. This study aims to analyze students’ learning motivation based on gender and to examine the correlation between gender representation in social studies instruction and the learning motivation of elementary school students. This study employed a qualitative approach using a case study design conducted at an elementary school in Purwakarta Regency. The research subjects consisted of two teachers and four students selected using purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using the Miles & Huberman model with triangulation of techniques and sources to enhance data validity. Students’ learning motivation generally fell into the “good” category. Female students’ learning motivation was generally more stable, while male students’ motivation was more influenced by the learning methods used. Social studies curriculum content also revealed an imbalance in gender representation; males were more frequently depicted in the public sphere, while females were depicted in the domestic sphere. There is a relationship between gender representation in social studies instruction and students’ learning motivation; therefore, teachers and instructional material developers need to pay attention to balanced gender representation and the use of varied teaching methods.